2012
DOI: 10.2147/amep.s34780
|View full text |Cite
|
Sign up to set email alerts
|

Learning strategies of medical students in the surgery department, Jeddah, Saudi Arabia

Abstract: ObjectivesTo identify medical students’ perceptions of their learning strategies including, learning habits, resources, and preferred teaching methods, in the Department of Surgery (DOS) of the King Abdulaziz University-Faculty of Medicine (KAU-FoM), in Jeddah, Saudi Arabia.MethodsA cross-sectional descriptive study which was designed to identify students’ perceptions of their learning in the DOS of the KAU-FoM. A questionnaire was administered to a random group of 549 medical students, to explore student perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The study showed that teachers should be well prepared before teaching ESP courses, students had to be motivated and elevate their English proficiency, and prescribed books taken prior to university study should introduce scientific topics. Alzahrani and Alzahrani (2012) identified another effective element of learning, related to medical students' perceptions of their learning strategies, including learning habits, learning resources, and preferred teaching methods. They utilized a questionnaire submitted to students and found that students preferred self-instruction and practical sessions over lecturing.…”
Section: Resultsmentioning
confidence: 99%
“…The study showed that teachers should be well prepared before teaching ESP courses, students had to be motivated and elevate their English proficiency, and prescribed books taken prior to university study should introduce scientific topics. Alzahrani and Alzahrani (2012) identified another effective element of learning, related to medical students' perceptions of their learning strategies, including learning habits, learning resources, and preferred teaching methods. They utilized a questionnaire submitted to students and found that students preferred self-instruction and practical sessions over lecturing.…”
Section: Resultsmentioning
confidence: 99%
“…The need for an innovative curriculum has been continuously highlighted in many studies [15,[46][47][48]9]. There are some recommended elements to accomplish the implementation in limited resources settings:…”
Section: Discussionmentioning
confidence: 99%
“…Integrated curriculums show improved comprehension [68,69]. Single-method curriculums should be avoided [15,67,46,47,48]. For this purpose, we encourage the aim of an integrated curriculum [70].…”
Section: Using An Integrated Approachmentioning
confidence: 99%
“…Studies on students' perceptions of mobile learning services have also provided valuable information on how students interact with and use m-learning applications. Customizing these technologies to successfully fulfill the requirements and preferences of students requires an understanding of their perspectives (Aginako and Guraya, 2021; Alzahrani et al ., 2012; Kagawa, 2007). Additionally, studies have examined the effects of different factors at various stages of usage on the expansion of mobile learning applications.…”
Section: Introductionmentioning
confidence: 99%